2022
DOI: 10.1038/s41598-022-12897-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic experiments of acid mine drainage with Rhodopseudomonas spheroides activated lignite immobilized sulfate-reducing bacteria particles treatment

Abstract: Aiming at the problem that the treatment of acid mine drainage (AMD) by sulfate-reducing bacteria (SRB) biological method is susceptible to pH, metal ions, sulfate and carbon source. Lignite immobilized SRB particles (SRB-LP) and Rhodopseudomonas spheroides (R. spheroides) activated lignite immobilized SRB particles (R-SRB-LP) were prepared using microbial immobilization technology with SRB, R. spheroides and lignite as the main substrates. The dynamic experimental columns 1# and 2# were constructed with SRB-L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…As indicated in Table 2 , a pH decrease was noted at the start of the experiment, particularly in CW2. Throughout the experiment, the continuous pH decrease in CW2 is linked to the presence of lignite, known for its pH-lowering effect due to its limited negative charge, reducing the removal action of H+ ions ( Di et al, 2022 ). The pH value from CW3 provides additional evidence supporting the pH decline observed in CW1 and CW2, attributed to the presence of lignite.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated in Table 2 , a pH decrease was noted at the start of the experiment, particularly in CW2. Throughout the experiment, the continuous pH decrease in CW2 is linked to the presence of lignite, known for its pH-lowering effect due to its limited negative charge, reducing the removal action of H+ ions ( Di et al, 2022 ). The pH value from CW3 provides additional evidence supporting the pH decline observed in CW1 and CW2, attributed to the presence of lignite.…”
Section: Discussionmentioning
confidence: 99%
“…A completely randomized design was used to explore the influence of five factors, namely, the type of coal gangue (1-4# CG), the dosage of coal gangue (20, 30, 40, 50 and .36 E) was taken as the seed mud, and the SRB was anaerobically cultured using Starkey medium [25,28]. SRB, after separation and purification, was used in this study.…”
Section: Completely Randomized Designmentioning
confidence: 99%
“…Xianjun Wang et al [27] showed that SRB can effectively remove SO 4 2− in AMD and improve the pH value of AMD. Junzhen Di et al [28] showed that SRB can efficiently repair AMD pollution and metabolize SO 4 2− to form metal sulfide precipitation. However, SRB is sensitive to the environmental pH value and concentration of heavy metal ions [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation